1992
DOI: 10.1007/bf00189520
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymorphism of HLA class II genes in primary biliary cirrhosis

Abstract: We investigated the DNA restriction fragment length polymorphism of the major histocompatibility complex class II genes: HLA-DRB, -DQA, -DQB, DPA, -DPB, the serologically defined HLA-A, B, C, DR antigens, and the primed lymphocyte typing defined HLA-DP antigens in 23 Danish patients with primary biliary cirrhosis (PBC) and in healthy Danes. The following genetic markers were found with increased frequencies in PBC: HLA-B8 (relative risk, RR = 2.4, P less than 0.05, 'corrected' P greater than 0.05), HLA-DR3 (RR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 24 publications
1
39
1
Order By: Relevance
“…A similar association between HLA-DR3 and PBC was found in a Danish study [20] which, however, did not find any increase in HLA-DR8 in their study population. Furthermore, HLA-A28 was weakly positively and HLA-DR5 was weakly negatively associated with PBC in the present study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A similar association between HLA-DR3 and PBC was found in a Danish study [20] which, however, did not find any increase in HLA-DR8 in their study population. Furthermore, HLA-A28 was weakly positively and HLA-DR5 was weakly negatively associated with PBC in the present study.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have reported an increased frequency of HLA-DR8 [16][17][18][19][20][21][22] and HLA-DR3 [20,23] in PBC patients compared to referent persons. In one study [16], HLA-DR5 had decreased frequency in PBC as compared to referent persons, and in another study [22], HLA DRB1*1302 (DR6) and HLA DRB1*1501 (DR2) were found to be negatively associated with PBC.…”
Section: Introductionmentioning
confidence: 99%
“…36 It is possible that positive association might be 41 This association was not confirmed in several other studies from different non-British European populations. 32,35,36,42,43 Moreover, other European studies suggested significant associations of PBC with DR3 29,35 and DPB1*0301, 44 while the most recent study from the United States demonstrated an association between DRB1*08-DQA1*0401-DQB1*04 haplotype and PBC, albeit in a minority of patients. 40 Finally, studies from Japan failed to provide a consistent picture of HLA class II associations with PBC.…”
Section: Mhc and Pbcmentioning
confidence: 97%
“…In the past, studies performed on small series of subjects (between 21 and 75) have examined the association between HLA class I molecules and PBC susceptibility, [29][30][31][32][33][34][35] but the conclusions of such earlier reports were affected by several major flaws. First, the small patient populations evaluated in these studies may account for a limited statistical power of comparisons.…”
Section: Mhc and Pbcmentioning
confidence: 99%
“…A limited amount of effort has been placed on assessing the potential association of HLA class I alleles with PBC, with a handful of small studies finding no associations (34)(35)(36)38,45,46,48). More recently, a few rare HLA-B alleles were found to be associated with PBC in an Italian study of 112 PBC patients and 558 controls (53).…”
Section: Mhc -Hlamentioning
confidence: 99%